A p-n Heterojunction Based Pd/PdO@ZnO Organic Frameworks for High-Sensitivity Room-Temperature Formaldehyde Gas Sensor - Khan, Faheem Ullah; Mehmood, Shahid; Liu, Shiliang; Xu, Wei; Shah, Muhammad Naeem; Zhao, Xiaojin; Ma, Junxian; Yang, Yatao; Pan, Xiaofang (Frontiers in Chemistry, 2021)
As formaldehyde is an extremely toxic volatile organic pollutant, a highly sensitive and selective gas sensor for low-concentration formaldehyde monitoring is of great importance. Herein, metal-organic framework (MOF) derived Pd/PdO@ZnO porous nanostructures were synthesized through hydrothermal method followed by calcination processes. Specifically, porous Pd/PdO@ZnO nanomaterials with large surfaces were synthesized using MOFs as sacrificial templates. During the calcination procedure, an optimized temperature of 500 °C was used to form a stable structure. More importantly, intensive PdO@ZnO inside the material and composite interface provides lots of p-n heterojunction to efficiently manipulate room temperature sensing performance. As the height of the energy barrier at the junction of PdO@ZnO exponentially influences the sensor resistance, the Pd/PdO@ZnO nanomaterials exhibit high sensitivity (38.57 % for 100ppm) at room temperature for 1-ppm formaldehyde with satisfactory selectivity towards (ammonia, acetone, methanol, and IPA). Besides, due to the catalytic effect of Pd and PdO, the adsorption and desorption of the gas molecules are accelerated, and the response and recovery time is as small as 256 and 264 seconds, respectively. Therefore, this MOF-driven strategy can prepare metal oxide composites with high surface area, well-defined morphology, and satisfactory room-temperature formaldehyde gas sensing performance for indoor air quality control.